Tantangan Pembelajaran Jarak Jauh (PJJ) di SDK Banua Kabupaten Enrekang - Khaeruddin Khaeruddin; Sri I Mansur; Feri Padli (Indonesian Journal of Social Science Education (IJSSE), 2022)
This research is motivated bythe problems faced during distance learning in areas where internet access is still minimal. This research was conducted to examine the conditions of distance learning, the challenges faced and the efforts made to maximize the learning process using a combination of online and offline methods at SDK Banua, one of the primary schools in Enrekang district. The research method used is a qualitative method with data collection techniques in the form of observation and interviews. The results of the study shows that the learning conditions in the Banua SDK use a combination of online and offline methods where in the online method teaching and learning activities are carried out via WhatsApp. While the offline method is carried out through visit to students homes to carry out the learning process. In addition, students are allowed to go to school only to pick up and collect assignments. During the implementation of distance learning, students are given more assignments to encourage student activity in learning. This learning model is used because internet access in Banua hamlet is not evenly distributed and there are still parents who do not have anroid.